Clozapine: the correlation between clinical improvement and laboratory parameters - Gosling, John Albert (University of the Free State, 1977)
In this study, fifteen Black patients suffering from acute schizophrenia were treated with clozapine for a period of 40 days in order to ascertain whether certain laboratory parameters could be utilized to give an indication of the clinical efficacy of clozapine treatment in these patients. S.l.l Therapeutic efficacy Utilizing the B.P.R.S. and F.C. rating scale as indication of the clinical improvement of the patients, it was found that significant clinical improvement occurred upto day 30 whereafter clinical improvement was only slight. Clozapine was well tolerated by all the patients while more than half the patients (53,3%) were fit for unmndhional discharge on completion .of the study. On completion of the study the working capacity of the majority (80%) was satisfactory. 5.1.2 Side effects The most common side effects encountered were daytime sedation which was especially prominent during the early stages of the study and hypersalivation which occurred with equal frequency throughout the study period. Other side effects encountered in descending order of frequency were nausea and vomiting, dizziness, headache, disturbance of visual accomodation, constipation and diarrhoea, disturbed sleep, sweating, inhibition of micturition, and collapse. 5.1.3 Blood pressure and pulse rate Clozapine had no significant' prolongated effect on blood pressure while a significant and sustained rise in pulse rate during the treatment period was noted. It is suggested that this rise in pulse rate could be utilized as a convenient clinical aid in checking patient compliance in patients being treated with clozapine. 5.1.4 Serum concentration of clozapine, clozapine plus metabolites, and metabolites only. 5.1.4.1 No correlation was found between serum levels of clozapine, clozapine plus its metabolites, or its metabolites only and clinical improvement. 5.1.4.2 It was found that on treatment day 5 steady state serum levels of clozapine and of clozapine plus it metabolites had been reached. 5.1.4.3 No auto-induction of the metabolism of clozapine appeared to occur during the treatment period. 5.1.4.4 No accumulation of clozapine or its metabolites appeared to occur during the treatment period. 5.1.4.5 It can be concluded that a certain period of exposure to a more or less constant serum level of clozapine and/or its metabolites is necessary to effect clinical improvement. 5.1.4.6 A significant correlation was found between the lying pulse rate and serum levels of clozapine plus its metabolites. The lying pulse rate can thus offer a reasonable indication of the expected serum levels of clozapine plus its metabolites. 5.1.5 Prolactin serum levels No rise in serum prolactin levels occurred in these patients after institution of treatment with clozapine. Therefore no correlation between clinical improvement and prolactin serum levels could be ascertained. 5.1.6 5-hydroxytryptamine-induced platelet aggregation No enhancement of 5-HT-induced platelet aggregation could be determined in these patients undergoing treatment with clozapine. Therefore no correlation could be established between clinical improvement and enhancement of 5-HT-induced platelet aggregation. 5.1.7 Plasma cholinesterase and red blood cell ace~- cholinesterase activitX' Both the plasma cholinesterase and red blood cell acetylcholinesterase activity fell within the normal range prior to the institution of treatment with clozapine. These parameters can therefore not be used as diagnostic aids in the diagnosis of schizophrenia. The activity of both parameters also fell within the normal range on conclusion of the study. It would thus appear that treatment with clozapine did not significantly affect these·.parameters.

Tydens hierdie studie is vyftien Swart pasiënte wat gely het aan akute skisofrenie behandel met klosapien vir 'n periode van 40 dae om vas te stelof sekere laboratorium parameters gebruik kon word om 'n aanduiding te gee van die kliniese bruikbaarheid van klosapien behandeling by hierdie pasiënte. 5.2.1 Terapeutiese bruikbaarheid Deur gebruik te maak van die Verkorte Psigiatriese Beoordelingskaal (B.P.R.S.) en die F.C. beoordelingsskaal om die kliniese verbetering van die pasiënte te beoordeel, is gevind dat betekenisvolle kliniese verbetering plaasgevind het tot op dag 30 waarna slegs 'n geringe verbetering plaasgevind het. Klosapien is goed verdra deur al die pasiënte terwyl meer as die helfte van die pasiënte (53,3%) geskik gevind is vir onvoorwaardelike ontslag ten voltooiing van die studie. Na voltooiing van die studie was die werksvermoë van die meeste pasiënte (80%) gevind om bevredigend te wees. 5.2.2 Newe-effekte Die mees algemene newe-effekte wat voorgekom het was sedasie (wat veral voorgekom het tydens die eerste deel van die studie) en hipersalivasie die voorkoms waarvan dieselfde gebly het gedurende die hele studie tydperk. Ander newe-effekte wat voorgekom het in volgorde van frekwensie (algemeen tot seldsaam) is naarheid en braking, duiseligheid, hoofpyn, versteuring van visuele akkommodasie, hardlywigheid en diaree, verstoorde slaap, sweet, inhibisie van urinering en kollaps. 5.2.3 Bloeddruk en polsspoed Klosapien het geen betekenisvolle uitwerking op bloeddruk gehad nie terwyl 'n betekenisvolle en volgehoue styging in polsspoed gedurende die behandelingstydperk waargeneem is. Dit word voorgestel dat hierdie verhoging in polsspoed gebruik kan word as 'n kliniese hulpmiddelom vas te stel of die pasiënt wel die medikasie neem in die geval van pasiënte wat met klosapien behandel word. 5.2.4 Serumkonsentrasie van klosapien, klosapien plus metaboliete en metaboliete alleen. 5.2.4.1 Geen korrelasie is gevind tussen serumvlakke van klosapien, klosapien plus metaboliete of die metaboliete alleen en kliniese verbetering nie. 5.2.4.2 Daar is gevind dat gelykvlak van klosapien en klosapien plus sy metaboliete reeds op dag 5 voorgekom het. 5.2.4.3 Geen outoinduksie van die metabolisme van klosapien blyk om voor te kom tydens die behandelings tydperk nie. 5.2.4.4 Geen akkumulasie van klosapien of sy metaboliete kom voor tydens die behandelingstydperk nie. 5.2.4.5 Die afleiding kan gemaak word dat 'n sekere tydperk van blootstelling aan 'n min of meer konstante serumvlak van klosapien en/of sy metaboliete.nodig is om kliniese verbetering teweeg te bring. 5.2.4.6 'n Betekenisvolle korrelasie is gevind tussen die liggende polsspoed en die serumvlakke van klosapien plus sy metaboliete. Die liggende polsspoed kan dus 'n aanduiding gee van die verwagte serumvlakke van klosapien plus sy metaboliete. 5.2.5 Prolaktien serumvlakke Geen verhoging in prolaktien serumvlakke het voorgekom nadat die pasiënte met klosapien behandel is nie, derhalwe kon geen korrelasie tussen kliniese verbetering en prolaktien serumvlakke aangetoon word nie. S.2r6 5-hidroksitriptamiengeïnduseerde plaatjiekleefbaarheid Geen versterking van 5-HT-geïnduseerde plaatjiekleefbaarheid kon vasgestel word in hierdie pasiënte wat met klosapien behandel is nie. Derhalwe kon geen korrelasie vasgestel word tussen kliniese verbetering en versterkte 5-HT-geïnduseerde plaatjiekleefbaarheid nie. 5.2.7 Plasmacholienesterase en rooibloedselasetielcholienesterase aktiwiteit Beide die plasmacholienesterase en rooibloedselasetielcholienesterase aktiwiteit was binne die normale perke voordat 'n aanvang geneem is met klosapienbehandeling. Hierdie parameters kan dus nie as diagnostiese hulpmiddels gebruik word by die diagnose van skisofrenien~.Die aktiwiteit van beide parameters het ook binne die normale perke geval na voltooiing van die studie. Dit blyk dus dat behandeling met klosapien nie hierdie parameters betekenisvol beïnvloed het nie.
Dissertation (M.Med.Sc. (Pharmacology))--University of the Free State, 1977
Keywords: Clozapine; Schizophrenia; Schizophrenia -- Treatment